2018
DOI: 10.1111/jipb.12723
|View full text |Cite
|
Sign up to set email alerts
|

Genomic divergence in cotton germplasm related to maturity and heterosis

Abstract: Commercial varieties of upland cotton (Gossypium hirsutum) have undergone extensive breeding for agronomic traits, such as fiber quality, disease resistance, and yield. Cotton breeding programs have widely used Chinese upland cotton source germplasm (CUCSG) with excellent agronomic traits. A better understanding of the genetic diversity and genomic characteristics of these accessions could accelerate the identification of desirable alleles. Here, we analyzed 10,522 high‐quality single‐nucleotide polymorphisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The Second introduction of tetraploid cotton into China was at the beginning of the 20th century when upland cotton was systematically introduced into China. During these years, cotton was mainly distributed in the Yangtze River region and the Yellow River region in China [7].…”
Section: Of 14mentioning
confidence: 99%
See 1 more Smart Citation
“…The Second introduction of tetraploid cotton into China was at the beginning of the 20th century when upland cotton was systematically introduced into China. During these years, cotton was mainly distributed in the Yangtze River region and the Yellow River region in China [7].…”
Section: Of 14mentioning
confidence: 99%
“…During recent years, cotton production has been mainly shifted to Xinjiang province. Prior to the introduction and implementation of Seed Law (SL) and Plant Variety Protection Act (PVPA) in China [8], most of the southwest varieties (introduced in early 20th century from the United States of America in the Yangtze River region and Yellow River region in China [7]) were maintained by farmers over the years. From this diverse southern gene pool, which is not only from different ecosystems but also has lower human intervention, useful information can be excavated to study the diversity of cotton crop in China through the evaluation of current Chinese varieties and their genetic background with reference to southern varieties and landraces from Central America.…”
Section: Of 14mentioning
confidence: 99%
“…Heterosis is that a hybrid is superior to two parents in one or more traits, and it is a common genetic phenomenon in nature [11]. Compared with the parental lines, CCRI63 showed superior performances in terms of lint percentage and boll weight.…”
Section: Discussionmentioning
confidence: 99%
“…In tomato, the overdominance model was proven, and revealed that heterozygous mutations perform better than homozygous ones [10]. In cotton, the researchers investigated the distribution of heterozygous loci among 12 commercial cotton hybrids, and suggested that heterozygous loci-enrichment may be responsible for the hybrid high yield performance and cotton heterosis was driven, in part, by these heterozygous sites [11].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study, based on SNP microarray, demonstrated the presence of extensive genomic divergence in the Upland cotton source germplasm and suggested that divergent genomic regions might be related to maturity and heterosis ( He et al, 2019 ). However, the origin of these regions is still unknown.…”
Section: Introductionmentioning
confidence: 99%